Management of Breast Lesions Detectable Only on MRI - Siegmann-Luz, K. C.; Bahrs, S. D.; Preibsch, H.; Hattermann, V.; Claussen, C. D. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Breast MR imaging has become established as the most sensitive imaging method for diagnosing breast cancer. As a result of the increasing examination volume and improved image quality, the number of breast lesions detected only on MRI and requiring further clarification has risen in recent years. According to the S3-guideline “Diagnosis, Therapy, and Follow-Up of Breast Cancer” as revised in July 2012, institutions performing breast MRI should provide the option of an MRI-guided intervention for clarification. This review describes the indications, methods and results of MRI-guided interventions for the clarification of breast lesions only visible on MRI. Recent guidelines and study results are also addressed and alternative methods and pitfalls are presented.Key points:Citation Format:
Keywords: breast; MR imaging; interventional MRI